Chemico-Pharmacological Screening of the Methanol Extract of Gynura nepalensis D.C. Deciphered Promising Antioxidant and Hepatoprotective Potentials: Evidenced from in vitro, in vivo, and Computer-Aided Studies - Nishan Chakrabarty; Hea-Jong Chung; Rashedul Alam; Nazim Uddin Emon; Safaet Alam; Mohammed Fazlul Kabir; Md. Minarul Islam; Seong-Tshool Hong; Tapas Sarkar; Md. Moklesur Rahman Sarker; Mohammad Manjur Rahman (Molecules, 2022)
Gynura nepalensis D.C. (family: Asteraceae) has abundant uses in the alternative medicinal practice, and this species is commonly used in the treatment of diabetes, rheumatism, cuts or wounds, asthma, kidney stones, cough, urinary tract bleeding, gall bladder stones, hepatitis, diarrhea, hemorrhoids, constipation, vomiting, fertility problems, blood poisoning, septicemia, skin allergy, indigestion, high cholesterol levels, and so on. This study aims to investigate the hepatoprotective and antioxidant potential of the methanol extract of the Gynura nepalensis D.C. (GNME) along with chemical profiling with phytochemical screening. Moreover, prospective phytocompounds have been screened virtually to present the binding affinity of the bioactive components to the hepatic and oxidative receptors. In the hepatoprotective study, alanine transaminase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total protein (TP), and lipid peroxidation (LP) and total bilirubin (TB) have been assessed, and in the antioxidant study, the DPPH free radical scavenging, total antioxidant flavonoid, and phenolic contents were determined. Moreover, the molecular binding affinity of the bioactive component of the plant has been analyzed using PyRx AutoDock Vina, Chimera, and Discovery Studio software. The plant extract showed dose-dependent hepatoprotective potential (p < 0.05, 0.01, 0.001) as well as strong antioxidant properties. Moreover, hepatoprotective and antioxidant molecular docking studies revealed a result varying from −2.90 kcal/mol to −10.1 kcal/mol. 4,5-dicaffeoylquinic acid and chlorogenic acid revealed the highest binding affinity among the selected molecules. However, the plant showed portent antioxidant and hepatoprotective properties in the in vitro, in vivo, and in silico models, and it is presumed that the hepatoprotective properties of the plant extract have occurred due to the presence of the vast bioactive chemical compounds as well as their antioxidant properties. Therefore, advanced studies are recommended to elucidate the pharmacological properties of the plant extracts.